2017
DOI: 10.1259/bjr.20170442
|View full text |Cite
|
Sign up to set email alerts
|

The evidence on effectiveness of weekly vs triweekly cisplatin concurrent with radiotherapy in locally advanced head and neck squamous cell carcinoma (HNSCC): a systematic review and meta-analysis

Abstract: The current evidence showed that weekly schedule is not superior to triweekly in improving oncological outcomes and decreasing early effects of treatment. In the absence of compelling data, triweekly schedule should remain the standard of care while more RCTs are warranted. Advances in knowledge: While some have proposed that low-dose weekly cisplatin is safer and less toxic, this study emphasized that there is no difference in acute toxicity of the two schedules and it is safe to utilize high-dose cisplatin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
4
28
1
1
Order By: Relevance
“…A recent meta-analysis including one randomized clinical trial and five retrospective studies revealed no overall survival and progression free survival difference comparing W-CP with B-CP. 17 In addition, this study did not reveal a difference between the regimens in terms of acute mucositis, acute dermatitis and severe renal events. A retrospective study performed in Turkey including 50 patients did not reveal a statistically significant difference in terms of toxicity between B-CP and W-CP with regard to renal, hematologic, skin, and GI toxicity.…”
Section: Discussionmentioning
confidence: 53%
“…A recent meta-analysis including one randomized clinical trial and five retrospective studies revealed no overall survival and progression free survival difference comparing W-CP with B-CP. 17 In addition, this study did not reveal a difference between the regimens in terms of acute mucositis, acute dermatitis and severe renal events. A retrospective study performed in Turkey including 50 patients did not reveal a statistically significant difference in terms of toxicity between B-CP and W-CP with regard to renal, hematologic, skin, and GI toxicity.…”
Section: Discussionmentioning
confidence: 53%
“…There are currently four meta-analyses/systematic reviews (Table 1) that should have provided a detailed, both quantitative and qualitative, synthesis of the existing data. [4][5][6][7] The data from the most recent study by Sturz et al from 2019 [8] are the same as ones published originally in 2017. [5] Different time periods focused upon in these meta-analyses naturally resulted in a different number and type of studies included (main and separate analysis), and consequentially a different patient number, unfortunately not always specified.…”
Section: Introductionmentioning
confidence: 70%
“…In spite of these shortcomings, it is remarkable to observe that there is no significant difference in not only OS, but LRFS, PFS, and RR as well. Regarding toxicity, while Guan et al [4] and Mohamed et al [7] found no difference in any of documented toxicities, Jacinto et al [6] found Grade >3 mucositis significantly more frequent in weekly CDDP, but only in a single RCT (using postoperative RT-CHT), while there was no difference in six retrospective studies using concurrent RT-CHT alone. In Sturz et al [5], the administration of CDDP every 3 weeks led to significantly more leucopenia, neutropenia, N&V and nephrotoxicity, with no difference in incidence rates of stomatitis and mucositis.…”
Section: Introductionmentioning
confidence: 95%
“…Patients receiving low-dose weekly cisplatin can be monitored for toxicity more often, allowing the schedule to be adjusted if needed. However, emerging evidence shows that this regimen might be suboptimal and should not be considered the standard of care [35,36]. a All patients received induction chemotherapy followed by concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%